The Effect of Reading the Qur'an on the Cognitive Function of the Elderly - L.Tobing, Yuni Valentri; Boy, Elman; Mukhtasor, Ahmad Shidqi; Furqoni, Aminullah (Universitas Muhammadiyah Semarang, 2022)
Background: The increasing population of the elderly can cause health problems in the elderly, including a decrease in cognitive function that is clearly visible in memory and intelligence. This can be prevented by doing activities that maximize brain power through increasing spiritual activities, such as reading the Qur'an.Objective: To determine the effect of reading the Qur'an on cognitive function in the elderly. The study population was 60 years of age or older, with an indicator of reading the Qur'an regularly every day. Cognitive function was assessed using the Mini-Mental State Examination (MMSE).Method: The type of literature study used is the literature review by assessing, identifying, and interpreting all findings on a research topic. Conducted using PubMed and Google Scholar restricted from 2010-2020. The keywords used in the article search were elderly, reading the Qur'an, and cognitive function. Results: Reading the Qur'an has a significant impact on the cognitive function of the elderly.Results: This study used seven journals, where five journals were obtained from Google Scholar and two journals from PubMed. Conclusion: From several studies collected, it can be concluded that the longer the duration (>15 minutes) and the more regularly the elderly read the Qur'an, the better their cognitive function.